Strategic human resource management and corporate social responsibility: Evidence from Emerging Markets - Rosolen, Talita; Maclennan, Maria Laura Ferranty (Internext, 2016)
Corporate social responsibility practices are increasingly being adopted and legitimized in business and they impact the strategic and operational levels in various areas. The integration of these criteria and practices in the strategic management involves many factors, and human resource management is an essential aspect for the accomplishment of such initiative. Thus, this paper associates the relationship among corporate social responsibility (CSR) various dimensions (strategic, ethical, social and environmental) and strategic human resource management (SHRM) in companies operating in Brazil. We also aim to identify whether there is impact of other aspects on this relationship, namely: size, industry and company internationalization level (if national or multinational). Results show evidence that ethical CSR can be associated to SHRM. Environmental CSR showed marginal relation, and social and strategic CSR presented no significant association. Those results emphasize the need to further develop strategic actions of CSR into human resource management in emerging markets. Managers can also benefit from those findings, as it is possible to have a broad view of limitations and opportunities regarding the role played by human resource management in CSR.